Dynamics of the dune-barrier and barrier islands of Patagones (Buenos Aires, Argentina) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Barriers and barrier islands can form from the reworking of coastal plains, non-operative deltaic plains, or by the growing of complex spits. They change their shape in relation to the sedimentation rates and the evolution of the sea level, but they are also very sensitive to man-made interventions, mostly when they cause variations in the littoral drift or sediment budgets. The barrier of Patagones is located in Northern Patagonia, and spans from the estuary of the Negro River to the former delta of the Colorado River; a coast dominated by a northward littoral drift. Part of the barrier is hanged on top of coastal cliffs, part is growing towards the depressed area of Anegada Bay, and the northern portion is being reworked from the former delta (Fig. 1). Landsat and CBERS images from different years, ALOS Palsar images and aerial photographs were analyzed in order to estimate morphologic changes of the dunes composing these barriers. Analogic and digital processes were applied to understand the evolution of both barriers. Climate (wind and rain) is the main factor that diminishes the sand supply to these dunes. Winds from the SW and W have a potential drift higher than 400 with a net transport towards the NE. The maximum migration rate of the dunes was 9 m a-1 (interval 1973-2005), higher than the migration rates estimated at other sand barriers of Buenos Aires Province. Near San Blas village, non-vegetated transverse-barchanoid dunes moved to the east (Fig. 3). Cliff-top dunes are present in Faro Segunda Barranca (Fig. 4). A great variation in the shape of parabolic dunes was observed between Punta Redonda and Punta Rasa (simple and compound) with a length-width relationship of 3 for simple elongated shapes (Fig. 5). Digital processing of Landsat images allowed calculating vegetation indices (NDVI) and change-detection maps, showing the fixation of 772 ha of dunes at the Punta Redonda- Punta Rasa area (1989-2005 period; Fig. 6). Prior to the Holocene transgression, several tectonic depressions were scattered on top of the plateau; two allochtonous rivers, the Colorado and Negro, crossed it. During the maximum highstand, the Negro River valley became flooded while a delta established where the Colorado River discharged into Anegada Bay (Fig. 9). In Jabalí Island, Upper Pleistocene marine terraces composed mostly of gravel were partially reshaped into beach ridges. In the last 6000 years, significant changes occurred. The avulsion of the Colorado River channels made it to discharge to the north during historic times. The delta became reworked by marine processes. The northward longshore drift accumulated the sand delivered by the Negro River that climbed on top of former cliffs along the segment between Faro Segunda Barranca and Punta Redonda. Westerly winds reinforced this eastwards sediment transport either as barchans or parabolic dunes. At the end of that littoral drift, at Jabalí Island, the sand transport induced dunes to climb on top of former Holocene beach ridges. The barrier islands of the north have been related to a decrease in the littoral transport, and an increase of the tidal prism that induced the stability of the tidal inlets.
Keywords: Barriers Dunes, Barrier Islands, Parabolic Dunes, Barchanoid Dunes, Patagones, Buenos Aires.